The considerable impact of the SARS-CoV-2 pandemic and COVID-19 on the UK National Mycology Reference Laboratory activities and workload. (14th July 2021) - Borman, Andrew M; Fraser, Mark; Patterson, Zoe; McLachlan, Sue; Palmer, Michael D; Mann, Ciara; Oliver, Debra; Brown, Phillipa; Linton, Christopher J; Dzietczyk, Agnieszka; Hedley, Michelle; Gough, Martin; et al.
Abstract: Starting late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a devastating global pandemic of coronavirus-19 disease (COVID-19) with ∼179 million cases and ∼3.9 million deaths to date. COVID-19 ranges from asymptomatic infection to severe illness with acute respiratory distress requiring critical care in up to 40% of hospitalized patients. Numerous reports have identified COVID-19-associated pulmonary aspergillosis (CAPA) as an important infective complication of COVID-19. In the UK, the pandemic has had unprecedented impacts on the National Health Service (NHS'): each wave of infections required hospitals to reconfigure for large surges in patients requiring intensive care, to the detriment of most aspects of non-COVID care including planned operations, outpatient appointments, general practitioner consultations and referrals. The UK National Mycology Reference Laboratory (MRL) offers a comprehensive service for the diagnosis and management of fungal disease nationwide, with a test portfolio that includes: diagnosis of allergies to fungal and other respiratory allergens; diagnosis of superficial and invasive/systemic fungal infections using traditional mycological, serological and molecular approaches; identification and susceptibility testing of the causative fungi; therapeutic drug monitoring of patients receiving antifungal therapy. Here, we describe the impact of the first 14 months of the COVID-19 pandemic on MRL activities. Changes to MRL workload closely mirrored many of the NHS-wide challenges, with marked reductions in 'elective' mycological activities unrelated to the pandemic and dramatic surges in tests that contributed to the diagnosis and management of COVID-19-related secondary fungal infections, in particular CAPA and candidemia in COVID-19 patients in intensive care. Lay summary: The COVID-19 pandemic has had an unprecedented impact on the UK National Health Service, with hospitals forced to repeatedly reconfigure to prepare for large surges in COVID-19 patients. Here we describe the impact of the first 14 months of the UK pandemic on the workload of the National Mycology Reference Laboratory.